Intracomplex general acid/base catalyzed cleavage of RNA phosphodiester bonds: the leaving group effect - Lonnberg T; Luomala M (ROYAL SOC CHEMISTRY, 2022)
The general acid/base catalyzed cleavage of a number of alkyl esters of uridine-3'-(and -5'-) phosphate has been studied by utilizing a cleaving agent, in which the catalytic moiety (a substituted 1,3,5-triazine) is tethered to an anchoring Zn-II: cyclen moiety. Around pH 7, formation of a strong ternary complex between uracil, Zn-II and cyclen brings the general acid/base catalyst close to the scissile phosphodiester linkage, resulting in rate acceleration of 1-2 orders of magnitude with the uridine-3'-phosphodiesters. Curiously, no acceleration was observed with their 5'-counterparts. A beta(lg) value of -0.7 has been determined for the general acid/base catalyzed cleavage, consistent with a proton transfer to the leaving group in the rate-limiting step.